Measuring Human Capital in Educaction - Stanislaw Walukiewicz; Aneta Wiktorzak (European Regional Science Association (ERSA), 2011)
We consider education as a number of multistage creative processes and analyse one of them - teaching knowledge (process P1) - in detail. In part 1 we describe the idea of Virtual Production Line (VPL), introduced by Walukiewicz in 2006 as an extension of Classical Production Line (CPL), an epitome of our perception of Henry Ford's assembly line. Teachers connected by modern ICT network (in most cases it will just be the Internet) provide education to students on a VPL - kind of a virtual belt - instructing a given set of subjects (tasks) in a prescribed sequence, offering knowledge by a prescribed methodology, etc. In contrast to CPL, teachers on VPL will use their brain power mostly and divide the teaching process into a number of tasks in what we will call `self-organization of VPL'. In that perspective, VPL shall be defined as a conscious experience of a division of labour into tasks (self-organization) via the Internet, while CPL will just remain a partition of labour into a fixed number of jobs (tasks). In part 2 we introduce the value of human capital of a given student as a measure of P1 efficiency and compare it with the indicators used so far. In Poland the problem is that, different skills of students are not measured within one, integrated system. We propose a solution to this problem. Field study results are furnished. In conclusion, we formulate suggestions for further research.
Keywords: 330; Human capital; Virtual Production Line (VPL); Classical Production Line (CPL); efficiency of education